On the Directionality of Cross-Linguistic Effects in Bidialectal Bilingualism - Castro, Tammer; Rothman, Jason; Westergaard, Marit (Frontiers in Psychology, 2017)
This study explores the interpretation of null and overt object pronouns by Brazilian Portuguese (BP) and European Portuguese (EP) bidialectal bilinguals. Object pronouns are a particularly good domain to examine, given that, particularly with respect to null objects, the underlying syntax as well as the semantic and discourse constraints that regulate their distributions in the two varieties are superficially different but inherently similar. We test the extent to which native BP speakers who moved to Portugal in adulthood and have lived there for a considerable time display cross-linguistic influence in either direction. Each subject is tested twice, once in BP mode and once in EP mode, which allows us not only to test if they have acquired the EP target structure but also to test the extent to which acquisition of EP might have consequences for the same domain in BP. Our results show that the high degree of typological proximity between the L1 and the L2 may contribute to L1 attrition and hinder target-like performance (i.e., processing) of L2 properties. We relate the findings to key theoretical questions and debates within the context of the larger field of bilingual studies, particularly with respect to L1 attrition and L2 acquisition.